Performance of cruciform column using universal beam sections under axial compression load - Md. Tahir, Mahmood; Shek, Poi Ngian (Penerbit UTM Press, 2005)
The main function of a column is to transfer loads by means of compressive action. The response of the column to a nominally applied load depends upon a number of factors. The most important are its length and cross-sectional shape, the strength of material, the conditions of support provided at its ends and the method of restrained to its axis. This paper presents the performance of cruciform column under axial compression load. Cruciform column, which is also known as compound members, consists of two universal beams section where one universal beam section is cut into two at the mid section of the beam and welded to the other beam section. The compression capacity tables based on the code BS5950-1:200 are developed for columns with different sections and different effective lengths. The study shows that the compression resistance of the column increases as the radius of gyration of the section increases due to the formation of cruciform column. The study also concludes that the use of cruciform column contributes to the saving of the column steel weights up to 35% compared to UC sections and up to 60% as compared to UB sections.